[Women sitting on the steps of Administration Building] (1953)
Label on negative sleeve reads 'Coeds in 55? (Sept. 1953)'. Women sitting on the steps of the Cal Poly administration building (now Cotchett Education), which was built in 1941. This photo was probably taken in September 1953. These women may be prospective students in 1953, when the Cal Poly administration was preparing to readmit women students. They are probably not Cal Poly students.